1994
DOI: 10.3109/08977199409010993
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of FGF-receptors Expressed by Stromal and Epithelial Cells Cultured from Normal and Hyperplastic Prostates

Abstract: Three fibroblast growth factors (FGFs), acidic FGF (FGF1), basic FGF (FGF2), and keratinocyte growth factor (FGF7) have been identified in prostate. To understand how FGFs regulate growth of the prostate, and to determine if regulation is altered in benign prostatic hyperplasia (BPH), the mitogenic potential of FGFs, receptor binding, and FGF-receptor (FGFR) gene expression of stromal (PS) and epithelial cells (PE) cultured from normal human prostate and BPH where determined. FGF1 and FGF2, but not FGF7, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 39 publications
3
41
1
Order By: Relevance
“…This suggests that FGF8, commonly secreted by epithelial cells, interacts with stromal tissue in a paracrine fashion. The prostate is known to express FGFR1, 2 and 3, while FGFR4 has only been detected at low levels in prostate cancer cell lines (Story et al, 1994;Ittman and Mansukhani, 1997;Giri et al, 1999;Ropiquet et al, 2000). In prostate carcinogenesis, FGFR splicing characteristics are known to be altered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that FGF8, commonly secreted by epithelial cells, interacts with stromal tissue in a paracrine fashion. The prostate is known to express FGFR1, 2 and 3, while FGFR4 has only been detected at low levels in prostate cancer cell lines (Story et al, 1994;Ittman and Mansukhani, 1997;Giri et al, 1999;Ropiquet et al, 2000). In prostate carcinogenesis, FGFR splicing characteristics are known to be altered.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that FGF8b, secreted by epithelial ×1000 ×1000 ×1000 ×2000 ×2000 (Story et al, 1994). Immunohistochemistry demonstrated that FGF8b protein was significantly overexpressed in locally advanced and high-grade tumours.…”
Section: Discussionmentioning
confidence: 99%
“…14 The FGF family members are mitogenic to both prostatic epithelial and stromal cells. 39 bFGF is produced mainly by stromal and, to a lesser extent, by epithelial cells 36,40 and participates in prostate growth regulation through an autocrine effect on stromal cells and a weak paracrine effect on epithelial cells. 41 Although FGF's role in BPH development is indisputable, it is still unknown at which stage(s) of BPH development bFGF exerts its effects.…”
Section: Discussionmentioning
confidence: 99%
“…The level of expression also correlates with tumour stage, pathological grade and disease specific survival (Dorkin et al, 1999). Furthermore the receptors for FGF8, namely FGFR2IIIc, FGFR3IIIc and FGFR4 are known to be expressed in malignant prostate epithelium (Story et al, 1994;Ittman and Mansukhani, 1997).…”
Section: Introductionmentioning
confidence: 99%